Telaah Metodologi Dan Pemikiran Ibn Katsir Tentang Ayat-Ayat Munakahat Dalam Tafsir Al-Qur’an Al-‘Azhim - M. Ridho Firdaus; Akmal Abdul Munir (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze in depth the methodology and characteristics of Imam ‘Imaduddin Abu al-Fida’ Isma’il ibn ‘Umar ibn Kathir’s (d. 774 AH) thinking in interpreting the verses on marriage in his monumental work, Tafsir Al-Qur’an Al-‘Azhim. As one of the most influential tafsir in the Islamic world, Ibn Kathir's thoughts on family issues have had a significant impact. This study uses qualitative methods with a library research approach and content analysis of Ibn Kathir's interpretation of key verses on marriage, polygamy, leadership in the household (qawamah), divorce, and the rights and obligations of husbands and wives. The results show that Ibn Kathir's main methodology is tafsir bi al-ma'tsur (interpretation based on tradition) which is hierarchical: interpreting the Qur'an with the Qur'an, then with the Hadith, then with the words of the Companions and Tabi'in. His thinking on munakahat issues tends to be textualist-normative, oriented towards fiqh (law), and heavily influenced by the views of the salaf scholars. As a result, Ibn Kathir's interpretation tends to be patriarchal, reflecting the socio-historical context of his time, but it remains a primary reference due to the wealth of historical data it presents.